2021
DOI: 10.1182/blood-2021-148849
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Neurological Complications Among Children with Sickle Cell Disease in the United States: Findings from the 2007-2018 National Health Interview Survey (NHIS)

Abstract: Background: In the United States , sickle cell disease (SCD), affects about 100,000 individuals, with roughly 2,000 babies born annually with SCD. African Americans are disproportionately affected by SCD. In addition to medical conditions, psychosocial and affective comorbidities are also observed in relation to the frequency and intensity of pain crises. Evidence also suggests robust academic challenges that begin in elementary school and persist until high school. It is estimated that about 25% to 33% of chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…The embedded EL facilitated NPT completion by providing education and identifying and addressing barriers for families. The high prevalence of specific learning disorders and ADHD diagnoses in our cohort is consistent with existing literature: the 2007–2018 National Health Interview demonstrated that Black children with SCD are more likely to have a learning disability, intellectual disability, or developmental delay than Black children without SCD 17 …”
Section: Discussionsupporting
confidence: 90%
“…The embedded EL facilitated NPT completion by providing education and identifying and addressing barriers for families. The high prevalence of specific learning disorders and ADHD diagnoses in our cohort is consistent with existing literature: the 2007–2018 National Health Interview demonstrated that Black children with SCD are more likely to have a learning disability, intellectual disability, or developmental delay than Black children without SCD 17 …”
Section: Discussionsupporting
confidence: 90%